Let‐7 and miR‐125 cooperate to prime progenitors for astrogliogenesis. (23rd February 2015) - Shenoy, Archana; Danial, Muhammad; Blelloch, Robert H
<x xml:space="preserve">Abstract</x> The coordinate action of multiple miRNAs is required to shape cellular gene expression profiles and facilitate transition from glial progenitor cells to astrocytes.